Volunteering and civic action: boundaries blurring, boundaries redrawn - Evers, Adalbert; Essen, Johan von (Voluntas, 2019)
The aim of this introduction to the special issue is to call into question the presumed conceptual divide between volunteering and civic action and suggest an analytical tool and four perspectives that bring to light the varying meanings of popular engagement. Volunteering and civic action are laden with different moral meanings, are associated with different theoretical approaches and, just as important, have been assigned different roles in society. This conceptual divide is reflected in the academic debate. Only rarely, however, has the academic debate explored and discussed how the meaning of volunteering and civic action has changed historically. Therefore, we argue for a contextual and relational interpretation of the different forms of popular engagement instead of the application of essentialist definitions of volunteering and civic action. In order to examine the variety of popular engagement without being caught up in pre-made or taken-for-granted conceptualisations of volunteering and civic action as two separate forms of popular engagement, we propose approaching variations of popular engagement with respect to two criteria: first, to what degree popular engagement is enacted in institutionalised spheres of politics or in social public spheres and, second, to what degree actions of popular engagement are controversial or operating in line with what is widely agreed upon and dominant in public opinion. Moreover, we argue that history, discourses, politics and a relational approach are four crucial perspectives in order to reveal the varying meanings of popular engagement.
Gesehen am 08.07.2019